2015
DOI: 10.1182/blood.v126.23.600.600
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Mutated Cancer-Associated Genes at Diagnosis in CML Patients with Early Transformation to Blast Crisis

Abstract: Background: A single genomic event is sufficient to cause CML; Ph translocation and the resulting BCR-ABL fusion. Additional genomic lesions accompany progression, which occurs very rapidly after diagnosis (dx) in a minority. Identification at dx of patients (pts) with poor prognosis remains an important goal and new sequencing technology enhances the prospects of uncovering pathologically relevant lesions for early warning of disease progression. Aim: To determine the somatic genomic landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…It is proposed that blast transformation of CML is triggered by molecular or genetic mutations, such as trisomy 8, trisomy 19, isochromosome 17, t(3;21), mutations in p53, RB gene, RAS pathway, or p16/ARF pathway mutations [5]. CML blast crisis of T-cell lineage can be difficult to differentiate from de novo BCR-ABL1-positive T-cell Acute Lymphoblastic Leukemia (T-ALL) and BCR-ABL1-positive bilineage leukemia [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that blast transformation of CML is triggered by molecular or genetic mutations, such as trisomy 8, trisomy 19, isochromosome 17, t(3;21), mutations in p53, RB gene, RAS pathway, or p16/ARF pathway mutations [5]. CML blast crisis of T-cell lineage can be difficult to differentiate from de novo BCR-ABL1-positive T-cell Acute Lymphoblastic Leukemia (T-ALL) and BCR-ABL1-positive bilineage leukemia [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic abnormalities associated with blast transformation include trisomy 8 and 19, isochromosome 17, t (3;21), and del17p [ 4 ]. The most frequent ACA observed in BC is ACA +8, +Ph, I (17q), +19, +21, +17 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations associated with blast evolution include RUNX1 (33.3%), ASXL1 (20.5%), and IKZF1 (17.9%) [ 6 ]. Branford et al reported six mutations (ASXL1, BCORL1, RUNX1, GATA2, MLL, and UBE2A) that were recurrently mutated in patients with CML and early blast transformation [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…U chorych w fazie BC obok mutacji w domenie kinazowej BCR-ABL1 jednocześnie pojawiały się mutacje w tzw. cancer genes, co wskazuje na złożoność mechanizmów progresji CML [18].…”
Section: Mutacje O Znaczeniu Prognostycznym Dla Odpowiedzi Na Leczenie Ikt I Oceny Ryzyka Progresji Chorobyunclassified